1972
DOI: 10.4141/cjas72-083
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Methane Inhibition in Ruminants (Steers)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 7 publications
3
18
0
Order By: Relevance
“…On the day 21 of every period, gas sample was collected at 0, 2, 4 and 6 h post‐feeding by a close‐fitting plastic tube, which was inserted in the rumen fistula, where the arm end was covered with two layers of cheesecloth and positioned above the ingesta. The other end of the tube was fitted with two layers of a plastic bag, ensuring no air coming inside before collecting gas (Johnson et al., modified by Poungchompu et al., ). Samples of gas were obtained via rubber tubing to a plastic bag by three times of rumen movement.…”
Section: Methodsmentioning
confidence: 99%
“…On the day 21 of every period, gas sample was collected at 0, 2, 4 and 6 h post‐feeding by a close‐fitting plastic tube, which was inserted in the rumen fistula, where the arm end was covered with two layers of cheesecloth and positioned above the ingesta. The other end of the tube was fitted with two layers of a plastic bag, ensuring no air coming inside before collecting gas (Johnson et al., modified by Poungchompu et al., ). Samples of gas were obtained via rubber tubing to a plastic bag by three times of rumen movement.…”
Section: Methodsmentioning
confidence: 99%
“…Adaptation to the chemicals occurred in some studies and the CH 4 mitigation effect became lower with time (Johnson et al 1972;Immig et al 1996). However, the effect of BCM appeared to be persistent (Sawyer et al 1974;Tomkins et al 2009;Abecia et al 2012).…”
Section: Mitigation Of Enteric Ch 4 Per Animal or Per Unit Of Digestimentioning
confidence: 99%
“…However, this approach is technically difficult, given the cumbersome techniques required to grow methanogens, their inherently slow growth kinetics and their extreme sensitivity to oxygen. Historically, a number of studies using various halogenated compounds have demonstrated the 'proof of principle' of small molecule inhibitors, especially in shorter-term animal experiments; however, unfortunately, the inhibitors are either unacceptable because of environmental or toxicology concerns, or tend to become less effective over time (Johnson et al, 1972;Czerkawski and Breckenridge, 1975;Van Nevel and Demeyer, 1995;McCrabb et al, 1997).…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%